2012
DOI: 10.1016/s1514-0326(12)60011-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhabitants' Willingness to Pay for Cultural Heritage: A Case Study in Valdivia, Chile, Using Contingent Valuation

Abstract: We estimate the economic value of the urban cultural heritage of Valdivia, Chile, an emblematic historical city that comprises an ensemble of disperse cultural heritage elements. To derive its economic value we use the preferences stated by residents. The contingent valuation method with parametrical estimation (probit bivariate models) is applied, consisting of a survey employing double-bounded questions. The paper contributes to broadening the spectrum of case studies in this line of research in developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 37 publications
0
11
0
5
Order By: Relevance
“…This conforms to the findings of previously published papers such as Abuamoud et al (2014) who reported that visitors to cultural heritage site in Jordan who had higher level of education would pay more to visit the site. In a Chilean study of residents' willingness to pay for a cultural heritage site, Båez-Montenegro et al (2012) found that residents who had higher level of education were willing to pay more for the site. This highlights the importance of education in designing strategy that promote access fee to Mount Wilhelm and raising awareness of its importance among residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conforms to the findings of previously published papers such as Abuamoud et al (2014) who reported that visitors to cultural heritage site in Jordan who had higher level of education would pay more to visit the site. In a Chilean study of residents' willingness to pay for a cultural heritage site, Båez-Montenegro et al (2012) found that residents who had higher level of education were willing to pay more for the site. This highlights the importance of education in designing strategy that promote access fee to Mount Wilhelm and raising awareness of its importance among residents.…”
Section: Discussionmentioning
confidence: 99%
“…There are several published papers that have shown that different factors influence willingness to pay (WTP) for nature based recreation. For example, distance of home to nature area (Ezebilo, 2014;Shang et al, 2012), income (Chen & Jim, 2010;Wang & Jia, 2012), proximity of alternative recreation sites (Mwebaze & Bennett, 2012;Abuamoud et al, 2014), access fee to recreation site (Casey et al, 2010;Cheung et al, 2014), gender (Kamiri, 2013), years of residence (Shang et al, 2012), age (Ransom & Mangi, 2010) education (Abuamoud et al, 2014;Båez-Montenegro et al, 2012), family size (Naeemifar et al, 2011) and travel cost (Hakim, 2011). Others are category of visitors (Chen & Llaw, 2012;Pandit et al, 2015) and dependency on natural resources (Tuan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This represents only 6.9%, substantially less than the two Macau studies referred to above (Jin, , 32% and Song et al, , 35%). It is also far lower than protest zeros reported in other studies of cultural goods, for example Bàez‐Montenegro et al (), approximately 21%, Del Saz Salazar and Montagud Marques (), 32%, and Giannakopoulou, Xypolitakou, Damigos, & Kaliampakos (), 42%. The open‐ended question as to why these respondents were not willing to forgo any of their wealth partaking payment showed that most attributed any current or future shortfall in funding for the orchestra to a failure on the part of the Macau government to use its revenue wisely.…”
Section: Resultsmentioning
confidence: 59%
“…Sobre isso, o autor Ribeiro (2004) destaca que a formulação de políticas públicas valoriza e aproveita os recursos culturais como forma de valorizar a imagem da festa e perpetuá-la, fato dependente dos interesses de meios oficiais de apoio e de setores com uma ampla visão cultural. Báez-Montenegro et al (2012) destacam que a valoração econômica do patrimônio histórico cultural constitui um desafio metodológico, uma vez que estudos estimam seu impacto econômico como atração turística, em que as pessoas estão conscientes do papel do patrimônio como criador de externalidades e apreciam-no como um elemento na identificação coletiva.…”
Section: Resultados E Discussõesunclassified